Multiplex high-resolution melting assay for simultaneous detection of five key bacterial pathogens in urinary tract infections: A pilot study - Kafi, Hossein; Emaneini, Mohammad; Halimi, Shahnaz; Rahdar, Hossein Ali; Jabalameli, Fereshteh; Beigverdi, Reza (Frontiers in Microbiology, 2022)
The diagnosis of urinary tract infections (UTIs) is usually based on the results of urine culture, but it is time-consuming, labour-intensive and has a low sensitivity. The aim of this study was to develop multiplex high-resolution melting assay (MHRM) for the simultaneous detection of five common bacterial pathogens (Escherichia coli, Klebsiella pneumoniae, Staphylococcus saprophyticus, Enterococcus faecalis, and group B streptococci (GBS)) directly from urine samples. A total of 287 urine specimens were evaluated by HRM assay and the results were compared with the conventional culture method. Five different melt curves generated and differentiated five bacterial pathogens. The detection limit of the MHRM assay was 1.5×103 CFU/ml for E. coli and K. pneumoniae and 1.5×102 CFU/ml for S. saprophyticus, E. faecalis and GBS. Compared to culture, the specificity of the MHRM assay ranged from 99.3% to 100%, and sensitivity 100% for all test pathogens. The MHRM assay developed in the current study might be functional tool for the diagnosis of UTIs and has the potential for direct detection of the organism in the clinical samples. Additionally, it creates results in less than 5 hours, helping clinicians to start treatment with appropriate antimicrobial agents. This method could be a useful supplement to urine culture.